Electrochemical Performance of Delafossite, AgFeO2: A Pseudo-Capacitive Electrode in Neutral Aqueous Na2SO4Electrolyte - Singh A.N.; Mondal R.; Rath C.; Singh P. (My University, 2025)
Layered delafossite AgFeO2 with open channel structure is envisaged as a pseudo capacitor electrode using Fe2+/Fe3+ redox couple. A simple co-precipitation method was employed for the phase formation of delafossite AgFeO2 resulting in a mixture of 2H and 3R-phase. Phase tuning of 2H phase was done by controlling the calcination conditions and characterizing by powder XRD, FT-IR, and Raman methods. 2H AgFeO2 was used to synthesize as a majority phase because it have the larger inter layer spacing than 3R phase shown. HRTEM study confirms the formation 2H phase in majority. All of the synthesized samples exhibit predominantly faradic battery-type redox behavior along with surface charge storage. Flower like microarchitectures of AgFeO2 show outstanding electrochemical performance with high specific capacity of 110.4 F g-1 at 1 A g-1 current density, that retained up to 89% after 2000th times charge/discharge in 1 M Na2SO4 electrolyte. In an asymmetric device mode, AFO-400//AC full cell exhibits superior electrochemical performance by delivering high energy density (33.5 Wh kg-1) and high power density (454.3 W kg-1) with excellent cycling stability (86% retention after 2000th cycles). The results clearly demonstrate that the synthesized delafossite AgFeO2 containing mixture of 2H and 3R-phases have remarkable potential to be used as a negative electrode material for supercapacitor and other energy storage technologies. © 2021 The Electrochemical Society ("ECS"). Published on behalf of ECS by IOP Publishing Limited.